『햄릿』 속 죽음의 장소를 통해 보는 죽음의 근대사 - 고근영(Keunyoung Ko) (영미연구, 2022)
본 논문은 프랑스 역사학자 필리프 아리에스(Philippe Ariès)가 분석한 서구 죽음관의 변천사 및 시대구분을 기준으로, 중세 이후 급격한 근대화를 거친 서구 문명의 죽음에 대한 태도가 르네상스를 대표하는 텍스트 『햄릿』(Hamlet) 속 주인공들의 애도 방식과 인물들이 죽어간 장소에 반영된 양상을 분석한다. 『햄릿』은 중세에서 근대로 넘어가는 과도기 속 영국 르네상스인들이 겪어야 했던 정서적 혼란과 트라우마를 주인공의 복합적 내면 정서로 은유하는 작품이다. ‘애도’를 핵심 주제로 하는 이 작품은 죽음에 대한 서구인들의 태도가 급격한 개인화의 과정을 거치며 근대화되는 과정을 다양한 층위에서 관찰할 수 있는 작품이다. 본 논문에서는 아버지 햄릿과 오필리어가 죽어간 장소와 그들이 애도되는 방식을 아리에스의 시대구분에 따라 검토함으로써, ‘길들여진 죽음’이 ‘자신의 죽음’으로, 다시 ‘타자의 죽음’으로 변모해가는 과정, 즉 중세적 죽음이 근대화되는 양상을 분석해본다. 아리에스의 분석에 근거해 햄릿의 애도를 죽음이 근대화되는 과정의 한 특징으로 읽을 때, 햄릿의 애도는 근대인에게 남겨진 중세적 정신의 잔재가 아닌, 진화하는 근대적 정신의 전형적 표상으로 다시 읽힐 수 있다. 이러한 주장의 텍스트적 근거를 찾기 위해, 본 논문에서는 작품 속에서 햄릿의 아버지나 오필리어 등의 죽음이 지나치게 애도되고 낭만화되는 방식을 그들이 죽어간 장소인 ‘정원’, ‘강물’ 등이 갖는 문화적 의미와 함께 고찰해볼 예정이다. Based on the history of the Western view of death and the division of the times analyzed by French historian Philippe Ariès, this paper examines how the modernization of Western attitudes toward death is reflected in the ways the main characters of Hamlet mourn the dead and in the places where its characters died. Hamlet is a work that metaphorizes the emotional confusion and trauma experienced by the British Renaissance people during the transition from the Middle Ages to the modern era with the main characters’ complex inner emotions. With mourning as the core theme, this work allows a multi-layered observation of the process of modernization of Western attitudes toward death which was in line with the personalization of modern minds. In this paper, by examining the place where Hamlet's father and Ophelia died and the way they were mourned according to Ariès' chronological classification, the process of “the Tame Death” being transformed into “the Death of the Self” and into “The Death of the Others” again; that is, the process of modernization of medieval death. This paper aims to read it again as a typical representation of the evolving modern spirit, not the remnants of the medieval spirit left to modern people, by reading Hamlet's mourning as a characteristic of the process of modernization of death based on Ariès' analysis. KCI Citation Count: 0